2007
DOI: 10.3386/w13109
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Corporation in its Place

Abstract: This article challenges the idea that the corporation is a globally superior form of business organization and that the Anglo-American common-law is more conducive to economic development than the code-based legal systems characteristic of continental Europe. Although the corporation had important advantages over the main alternative form of organization (partnerships), it also had disadvantages that limited its appeal to small-and medium-sized enterprises (SMEs). As a result, when businesses were provided wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 44 publications
0
56
1
2
Order By: Relevance
“…The empirical evidence on this form suggests it was not as widespread as claimed. See Guinnane et al 2007. Estadístico Histórico as well as the Anuarios Estadístico de Spain, that the Andino code led to the creation of about forty corporations (M. Bernal, 2004, p. 77) At the end of the 1840s the government suspended the 1829 code and related commercial law.…”
Section: The Legal Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical evidence on this form suggests it was not as widespread as claimed. See Guinnane et al 2007. Estadístico Histórico as well as the Anuarios Estadístico de Spain, that the Andino code led to the creation of about forty corporations (M. Bernal, 2004, p. 77) At the end of the 1840s the government suspended the 1829 code and related commercial law.…”
Section: The Legal Frameworkmentioning
confidence: 99%
“…Lamoreaux and Rosenthal (2005) show in the context of failed attempts to introduce the limited partnership in the U.S. that the common law can also produce conservatism: if judges are uneasy with a legal innovation, they can construe the new law so narrowly as to make the innovation useless as a real reform. Similarly, Guinnane, Harris, Lamoreaux and Rosenthal (2007) note that a few U.S. states introduced a form similar to the German Gesellschaft mit beschränkter Haftung (GmbH) in the 1870s (before the "real" GmbH was introduced in 1892), but that the form was never really used. They argue that this reflects the combination of common-law interpretation and federalism; judges in one state held the new form to be a corporation, while judges in other states held it to be a partnership, making it difficult for business people to know how the law would treat their investments if they used the new form.…”
mentioning
confidence: 99%
“…It was removed in the incorporation law of 1870, yet the high nominal share value of Mark 1,000 for a single share limited the number of possible owners. In 1892 corporate law was expanded by limited liability companies (GmbH); German trade law was now as advanced as the British from 1856 (Harris 2000;Johnson 2010;Freeman et al 2012;Guinnane et al 2007). …”
Section: Economic Accessmentioning
confidence: 99%
“…Namely, differentiating companies is important for several reasons as it provides protection of frequently opposite interest. First of all, the interests of the company itself are protected, and it is really important for the company to build its business image (goodwill) via its business name which will make it recognizable for business associates, clients and consumers (Guinnane, 2007). Also, the interests of consumers and clients are protected this way.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these theories are out of date because EP 2016 (63) 4 (1323-1332) Ivan Bulatović, Sanja Škorić, Vladimir Jovanović of the needs and requirements of contemporary business operations in the world, arguments may still be found that the independence of companies is merely a political decision set by law (Jovanović, 1990). The world trend is to observe companies as completely independent from the founder as legal entities with their own interests which may differ from the interests of owners as well as opposed to them (Guinnane, 2007). If a company is observed this way, then it represents an independent legal entity separated from its owners, founded in order to perform business activities and to make profit.…”
Section: Introductionmentioning
confidence: 99%